Jokowi's cabinet reshuffle : will it beat COVID-19? - Borsuk, Richard (2021)
President Joko Widodo has reshuffled his cabinet in a bid to better manage efforts to combat the COVID-19 pandemic and end the country’s recession. For the first time, Indonesia will have a health minister who is not a doctor.